Table of Content - - (Arab Journal for Sciences and Research Publishing, 2023)
Table of Content: 1. The purposes of The Holy Qura’n in the instruments of gaining wealth Lecturer. Mohammed Abdulrab Sharaf Lutf, Prof. Zakaria Hama 2. The reasons for intellectual differences from the perspective of Islamic law, and the role of Saudi universities in confronting them Dr. Sekina Mohamed Mohamed Abd El Halim, Dr. Amal Abd El Aziz Mohamed Ghazy 3. Semiotics of the Saudi heritage in the light of contemporary technology Lecturer Manal Eid Sanusi Abjabal, Co-Prof. Foton Fouad Fayoumi 4. The effects of the Corona pandemic on the current and future situation of organizing and holding events and occasions: a field study on the General Entertainment Authority in Kingdom of Saudi Arabia Mr. Rayan Abdul-Aziz Iraqi, Mr. Shaheen Sulaiman Al-Abdali, Dr. Mansour Talal Abid Alansari 5. Spatial analysis of residential land prices in Jeddah city Mr. Alsharif Shaker Abdullah 6. Palestinian Scientific Research from the Perspective of Master’s Students: Exploring Reality and Aspirations Dr. Osama Matar1, Dr. Reem Jawabreh, Mrs. Haya Radwan, Mr. Abedelrahman Alhajhamad, Dr. Mohammad Ayyash, Mrs. Sherin Kaleef, Mr. Thaher Gharabeh, Dr. Ashraf Abualrob, Mrs. Aseel Halabi, Mr. Diya Abu Shomer 7. Piecewise Linear Discontinuous Petrov Galerkin Method for Time Fractional Diffusion Equations Dr. Basheer Saleh Abdallah